Utilização da técnica de realce por manganês em ressonância magnética no estudo da epilepsia induzida por pilocarpina - Malheiros, Jackeline Moraes [UNIFESP] (2010)
Recently, there is renewed interest in combining MRI relaxation effects of Mn2+ in temporal lobe epilepsy (TLE) models. Manganese-enhanced magnetic resonance imaging (MEMRI) could act as surrogate marker of calcium influx into cells and trace neuronal connections, suggesting that it can act as imaging marker of epileptic focus. The aim of this study was to investigate changes in the manganese enhanced contrast evaluated by image acquisitions in the acute and chronic phases of the pilocarpine model of TLE. At the acute phase, the MEMRI signal intensity was analyzed at three different time points after the beginning of SE (Status epilepticus): 5, 15 or 30 minutes. The SE 30 minutes group diminished MEMRI signal intensity in CA1 and dentate gyrus (DG). There were no differences between control and the other groups. The c-fos expression accessed in the same animals indicated that 5 minutes of SE is sufficient to cause maximal cellular activity. At the chronic phase of pilocarpine model, the aim was to compare the mossy fiber sprouting (MFS) and the MEMRI hiperintensity in dentate gyrus (DG) in animals co-treated with cycloheximide (CHX). The co-administration of the protein synthesis inhibitor CHX blocked the MFS in some animals and did not prevent subsequent epileptogenesis. The results indicate a strong correlation between MFS and MEMRI hiperintensity for CHX+pilocarpine group (r=0,864) as well as for pilocarpine and control groups (r=0,78). The results are in agreement with the proposal that MEMRI hiperintensity are correlated to MFS in chronic model of TLE, even in CHX+pilocapine-treated animals.